2019
DOI: 10.1111/liv.13942
|View full text |Cite
|
Sign up to set email alerts
|

HEV in pregnancy: Understanding the crucial role of steroid hormones

Abstract: See Article on Page 633

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…On the other hand, these studies include 94,386 female (40%) and male (60%) blood donors, which represent a representative cohort. Sex differences could be related to HEV exposure, such as potentially higher rates of consumption of insufficiently heated pork in men [ 4 , 15 ], hormonal differences affecting the immune system [ 16 ] or socioeconomic factors, and the distribution of different genders in different occupational groups. The increasing HEV PCR positivity rate we observed was caused by European countries only.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, these studies include 94,386 female (40%) and male (60%) blood donors, which represent a representative cohort. Sex differences could be related to HEV exposure, such as potentially higher rates of consumption of insufficiently heated pork in men [ 4 , 15 ], hormonal differences affecting the immune system [ 16 ] or socioeconomic factors, and the distribution of different genders in different occupational groups. The increasing HEV PCR positivity rate we observed was caused by European countries only.…”
Section: Discussionmentioning
confidence: 99%
“…However, hormonal and immunological factors but also genetic factors seem to be of relevance. Steroid hormones which are elevated during pregnancy are known for their immunosuppressive properties and have been reported to enhance viral replication [67,70,71]. Bose et al suggested a link between diminished expression of the progesterone receptor and fatal outcome of hepatitis E in pregnant women [72].…”
Section: Acute Hepatitis Ementioning
confidence: 99%
“…It was furthermore shown that HEV replication occurs in human placenta, and is associated with fetal and maternal mortality in patients with ALF [74]. In summary, multiple hormonal factors seem to influence the clinical course and outcome of HEV infections and thus further studies are needed, investigating the role of genetic HEV variants, hormonal and immunological factors as well as genetic host factors [71].…”
Section: Acute Hepatitis Ementioning
confidence: 99%
“…Further research is needed to reveal the interactions between various hormones and viruses in the body during pregnancy. [26] HEV may contribute to immunocompromised patients (e.g., solid organ transplant [SOT] patients, [27] patients receiving chemotherapy for hematological malignancies, [28] patients with rheumatism using steroids and other immunosuppressive drugs, [29] and patients with Human Immunodeficiency Virus [HIV] [30] ) develop chronic hepatitis. To date, all chronic infection cases are caused by HEV3 and HEV4, and no related report of HEV1 or HEV2 exists.…”
Section: Clinical Manifestations Diagnosis and Pathologymentioning
confidence: 99%